Cognitive and motor perturbations in elderly with longstanding diabetes mellitus - Diaz Gerevini, Gustavo Tomás (2014)
Type 2 diabetes mellitus is a chronic disease characterized by insulin resistance; inflammation; oxidative stress; vascular damage; and dysfunction of glucose, protein, and lipid metabolisms. However, comparatively less attention has been paid to neurologic alterations seen in elderly individuals with type 2 diabetes. We review clinical, metabolic, and biochemical aspects of diabetic encephalopathy (DE) and propose that quality of dietary lipids is closely linked to DE. This implies that preventive nutritional interventions may be designed to improve DE.